Pengaruh Ekuitas Merek cosmicTerhadap Keputusan Pembelian Konsumen Pada cosmic 21 industries Bandung - Yusuf Tanjung; Taufik Nugraha (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
Blackjack 21 industries is a Company which walk in ready made clothes area  Clothing with system sale of retail, konsinyasi and buy to break. Gain strength the quality of brand an product, gain strength its fascination to dribble consumer chosen the product. Managing brand equity can improve excellence compete. In consequence, company owning strong brand earn more grab business exist in comparing company which do not have strong brand, so also conducted by cosmic21 industries Bandung.As for intention of this research is to knowing responder comments concerning brand equity of cosmicat cosmic21 industries Bandung, knowing decision of purchasing of consumer at cosmic 21 industries Bandung, and know the level of brand equity have an effect on to decision of purchasing of consumer at cosmic 21 industries Bandung.Method which is used in this research is descriptive research and verifikatif, while technique withdrawal of sampel use technique of sampel Aksidental is so that obtained by the amount of consumer taken as responder counted 80 one who represent consumer of cosmic 21 industries Bandung, data collecting method the used is observation, interview, kuesioner, documentation study and literature study. Here in after to know brand equity have an effect on to decision of purchasing of consumer at cosmic21 industries Bandung hence  by statistical test by using analysis of regresi linear modestly, where to facilitate data processing of writer use SPSS 13.0 Windows for.From spreading of kuesioner known that brand equity of cosmichave strong so that can form decision of purchasing of consumer. Pursuant to result of examination of statistic got that brand equity have an effect on signifikan to decision of purchasing of consumer with correlation number of r= 0.563. Where level of brand equity have an effect on to decision of purchasing of consumer equal to 31,7 % and the rest equal to 68,3% influenced by other factor which do not in research by writer like that is Brand Image, Brand Extensions and also Product Image.  Keyword : Brand Equity, Decision Purchasing of Consumer